Respostas imunes primária e secundária de células mononuclearesdo sangue periférico, in vitro, de indivíduos não infectados e de pacientes com doença de Chagas, estimuladas com antígenos de Trypanosoma cruzi - Vladimir Martins Pinheiro (2007)
The immune system (IS) as others has physiological functions that works toward the maintenance of homeostasis. During the acute phase of the infection by Trypanosoma cruzi, the IS functions intensively to eliminate the parasites that are able to leave the peripheral blood becoming predominantly intracellular favoring, therefore, the its maintenance and the development of the chronic phase of the disease. The objective of this work was to evaluate the ability of the IS of NI or individuals with Chagas disease to react in vitro to T. cruzi antigens. This was evaluated by the analysis of the expression or secretion of molecules involved on the process of activation or regulation of the response induced by the stimuli. Peripheral blood mononuclear cellsof the individuals included in this study were fractionated and evaluated before and after in vitro culture. Cells and supernatants from these cultures were collected at time zero (before antigenic stimulation) and at 2, 6 and 24 hours after antigenic stimulation for analysis of CD25, CD28 e CTLA-4 expression on the surface of T CD4+ and CD8+ cells as well as the levels of prostaglandins E2 and the cytokines IL-2, IL-10 and IFNg.The results show that T. cruzi antigens stimulate PBMC from NI to secrete IL-10 and PGE2 besides the induction of higher fluorescence intensity of CD25 in CD4+ cells. IL- 10 is detectable early in cell cultures of IND patients and remains high for the time period of the study, while IFNg was detected only at 12 h, in contrast with PBMC from CARD where IL-2, IL-10 and IFNg where detectable at all time points. In stimulated cultures, the mean fluorescence intensity of CTLA-4 was high in CD4+ T cells from theIND group while in the CARD group the antigenic stimuli induced higher CD25 mean fluorescence intensity in CD4+ and in CD8+ cells. Admitting the possibility that regulation induced by the stimuli in the IND is mediated by IL-10 and expression of CTLA-4, impairing the second cell activation signal, the absence of early secretion of this cytokine by cells from CARD may be one of the major factors related to the lack ofimmuno regulatory activity in these patients,. Furthermore, the secretion of regulatory molecules IL-10 and PGE2 by cells from NI individuals favors our interpretation that the IS also induces homeostasis in situations where immune response memory is not specific.